PtCu-coated BSA nanoparticles and preparation method and application thereof

By wrapping BSA on the surface of porous PtCu-based nanoparticles and using PtCu@BSA nanoparticles under an alternating current field, the adverse events and drug resistance problems of antibiotic treatment in osteomyelitis treatment were solved, and more efficient bacterial killing and inflammation regression was achieved.

CN119157852AActive Publication Date: 2024-12-20HEBEI UNIV OF TECH

Patent Information

Application Number
CN202411297992.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing treatment methods for osteomyelitis rely on antibiotics to treat adverse events and bacterial resistance, making it difficult to effectively improve the therapeutic effect of osteomyelitis.

Method used

Using PtCu@BSA nanoparticles, BSA is encapsulated on the surface of porous PtCu-based nanoparticles to enhance biocompatibility and stability, and catalyze the decomposition of water into hydroxyl radicals under the alternating current field, killing bacteria, and releasing positive ions to regulate the Infection with the microenvironment.

Benefits of technology

It improves antibacterial effect and drug stability, reduces the frequency of administration, improves the limitations of osteomyelitis treatment, enhances the killing ability of bacteria and reduces inflammation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119157852A_ABST
    Figure CN119157852A_ABST
Patent Text Reader

Abstract

The invention discloses PtCu-coated BSA nanoparticles as well as a preparation method and application thereof, and relates to the technical field of nano materials. According to the PtCu-coated BSA nano-particle, the porous PtCu-based nano-particle serves as a framework, the surface of the porous PtCu-based nano-particle is wrapped with BSA, the biocompatibility and stability of the PtCu-coated BSA nano-particle are enhanced, meanwhile, the porous PtCu-based nano-particle has high targeting capacity and electrodynamic force catalysis effect, water can be well catalyzed to be decomposed into hydroxyl free radicals under the action of an alternating current electric field, and therefore the water-soluble PtCu-coated BSA nano-particle can be used for preparing the water-soluble PtCu-coated BSA nano-particle. Therefore, bacteria are effectively killed, and the limitation that antibiotics are frequently used in existing medicines for treating osteomyelitis is improved. Meanwhile, in the electrodynamic catalysis process, the porous PtCu-based nano-particles can be partially degraded into positively charged ions such as Pt < 2 + >, Pt < 4 + > and Cu < 2 + >, and the ions have high biological membrane penetrability and can cooperatively regulate the infected microenvironment so as to subside local inflammation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomaterials, and in particular to PtCu@BSA nanoparticles and a preparation method and application thereof. Background Art

[0002] Osteomyelitis is an infection and destruction of bone caused by aerobic or anaerobic bacteria, mycobacteria, and fungi. Osteomyelitis often occurs in the long bones, the feet of patients with diabetes, or at the site of penetrating bone injury due to trauma or surgery. The most common site in children is the metaphysis of a well-vascularized long bone, such as the tibia or femur.

[0003] Literature review shows that the deep infection rate after open fractures in various parts of the body is 2% to 50%. The tibia is the most common site of open fractures and the most common site of bone infection. Research results show that the most common site of osteomyelitis is the lower limbs (accounting for 65%). Although the upper limbs are not as common as the lower limbs in osteomyelitis, they are also susceptible to secondary infection of the injured surface of traffic accidents. In addition, the incidence of spinal osteomyelitis is also high.

[0004] The current treatment for osteomyelitis is mainly through the use of antibiotics and surgical debridement of the osteomyelitis site. Common drugs include glycopeptides, such as vancomycin and teicoplanin, which are considered to be the main drugs against MRSA in the treatment of osteomyelitis. Both drugs are only available in parenteral preparations. Vancomycin can be used as the first choice drug due to its long history of use. However, it has an increased risk of adverse events, especially acute renal failure, especially in patients with other risk factors, such as concomitant use of nephrotoxic drugs, high serum trough concentrations or long-term administration, and frequent use of antibiotic treatment can cause bacteria to develop resistance and reduce the treatment effect. Therefore, how to improve the drugs for the treatment of osteomyelitis is an urgent problem to be solved.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a PtCu@BSA nanoparticle and a preparation method and application thereof.

[0007] The present invention is achieved in that:

[0008] In a first aspect, the present invention provides a PtCu@BSA nanoparticle, which comprises a porous PtCu-based nanoparticle and BSA, wherein the BSA is coated on the surface of the porous PtCu-based nanoparticle.

[0009] In an optional embodiment, the pore size of the porous PtCu-based nanoparticles is 10 to 50 nm;

[0010] Preferably, the porous PtCu-based nanoparticles are synthesized using Pluronic F-127 as a template.

[0011] In an optional embodiment, the loading amount of the BSA is 0.1 to 5 mg of the BSA per 1 mg of the porous PtCu-based nanoparticles;

[0012] Preferably, the encapsulation efficiency of BSA is 130-150%;

[0013] Preferably, the particle size of the PtCu@BSA nanoparticles is 110-120 nm;

[0014] Preferably, the potential of the PtCu@BSA nanoparticles is -20 to -10 mV.

[0015] In a second aspect, the present invention provides a method for preparing the PtCu@BSA nanoparticles as described in any one of the aforementioned embodiments, wherein the BSA is coated on the surface of the porous PtCu-based nanoparticles.

[0016] In an optional embodiment, the method for preparing the porous PtCu-based nanoparticles comprises: synthesizing using Pluronic F-127 as a template;

[0017] Preferably, the method for preparing the porous PtCu-based nanoparticles comprises dissolving chloroplatinic acid, cupric chloride, Pluronic F-127 and acid in a mixed solution, adding an α-ascorbic acid aqueous solution, heating the mixed system to react, reacting the solution until the solution turns black, and separating the solid from the liquid to obtain the porous PtCu-based nanoparticles;

[0018] Preferably, the reaction temperature of the mixed system is 90-100°C and the reaction time is 3-5h;

[0019] Preferably, the concentration of the α-ascorbic acid aqueous solution is 0.1-0.3M;

[0020] Preferably, the concentration of chloroplatinic acid is 15-25 mM, more preferably 20 mM.

[0021] Preferably, the concentration of the copper chloride is 15-25 mM, more preferably 20 mM.

[0022] Preferably, the concentration of Pluronic F-127 is 7.4-7.6 mg / mL, more preferably 7.4 mg / mL;

[0023] Preferably, the concentration of the acid is 4-8M.

[0024] In an optional embodiment, coating the BSA on the surface of the porous PtCu-based nanoparticles comprises:

[0025] dissolving the porous PtCu-based nanoparticles in an organic solvent, adding lipoic acid, and obtaining PtCu-COOH nanoparticles;

[0026] The PtCu-COOH nanoparticles are dissolved in water, and the BSA is added and stirred to obtain PtCu@BSA nanoparticles.

[0027] In an optional embodiment, the organic solvent includes C1-C4 low-carbon alcohol;

[0028] Preferably, the mass ratio of the porous PtCu-based nanoparticles to the lipoic acid is 1:8-12; the mass ratio of the porous PtCu-based nanoparticles to the BSA is 1:8-12;

[0029] Preferably, the reaction time of the porous PtCu-based nanoparticles and the lipoic acid is 10 to 15 hours; the reaction time of the PtCu-COOH nanoparticles and the BSA is 10 to 15 hours.

[0030] In an optional embodiment, before adding the BSA, the method further comprises adding EDC and NHS to the aqueous solution containing the PtCu-COOH nanoparticles;

[0031] Preferably, the total added mass of the EDC and the NHS is 5 to 15 times that of the PtCu-COOH nanoparticles;

[0032] Preferably, after obtaining the PtCu-COOH nanoparticles, they are washed and purified using an organic solvent;

[0033] Preferably, after obtaining the PtCu@BSA nanoparticles, they are washed and purified with deionized water.

[0034] In a third aspect, the present invention provides use of the PtCu@BSA nanoparticles described in any one of the aforementioned embodiments or the method for preparing the PtCu@BSA nanoparticles described in any one of the aforementioned embodiments in preparing a drug for treating osteomyelitis.

[0035] In a fourth aspect, the present invention provides a pharmaceutical composition for treating osteomyelitis, comprising the PtCu@BSA nanoparticles as described in any one of the aforementioned embodiments;

[0036] Preferably, the pharmaceutical composition for treating osteomyelitis further comprises a pharmaceutically acceptable excipient;

[0037] Preferably, the pharmaceutically acceptable excipients include one or more of solvents, solubilizers, cosolvents, emulsifiers, colorants, disintegrants, fillers, osmotic pressure regulators, stabilizers, glidants, flavoring agents, antibacterial agents, suspending agents, coating agents, antioxidants, antioxidant synergists, chelating agents, pH regulators, adsorbents, protective agents, humectants, softeners, absorbents, diluents, empty capsules, matrix and carrier materials;

[0038] Preferably, the dosage form of the pharmaceutical composition for treating osteomyelitis includes an injection form or an oral dosage form.

[0039] The present invention has the following beneficial effects:

[0040] The PtCu@BSA nanoparticles provided by the present invention use porous PtCu-based nanoparticles as a skeleton, and the surface of the nanoparticles is coated with BSA. Modifying the surface of the porous PtCu-based nanoparticles with BSA is beneficial to enhancing the biocompatibility and stability of the PtCu@BSA nanoparticles. At the same time, the porous PtCu-based nanoparticles have a high electrokinetic catalytic effect. Under the action of an alternating current electric field, they can well catalyze water decomposition into hydroxyl radicals, thereby effectively killing bacteria and improving the limitation of the frequent use of antibiotics in existing osteomyelitis treatment drugs. At the same time, during the electrokinetic catalytic process, the porous PtCu-based nanoparticles will partially degrade into positively charged ions such as: Pt 2+ , Pt 4+ , Cu 2+ , these ions have strong biomembrane penetration, these ions can synergistically regulate the infection microenvironment to reduce local inflammation. Compared with small molecule drugs, PtCu@BSA nanoparticles have better stability in the body, so they can increase drug circulation time and reduce the frequency of administration. PtCu@BSA nanoparticles are different from other drug carriers because of their ability to be activated under electric fields and their independent release of drugs. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0042] Figure 1 Transmission electron microscopy image (a) of PtCu prepared in Example 1, transmission electron microscopy image (b) of PtCu@BSA nanoparticles, and particle size distribution diagram (c);

[0043] Figure 2This is the XRD peak diagram of PtCu@BSA prepared in Example 1;

[0044] Figure 3 The infrared absorption peak diagram of PtCu@BSA, PtCu and BSA prepared in Example 1;

[0045] Figure 4 Transmission electron microscopy image (a) and particle size distribution diagram (b) of the porous PdCu-based nanoparticles prepared in Comparative Example 1;

[0046] Figure 5 Transmission electron microscopy image (a) and particle size distribution diagram (b) of the large mesoporous PtNPs nanoparticles prepared in Comparative Example 2;

[0047] Figure 6 Schematic diagram of the degradation of methylene blue for different examples;

[0048] Figure 7 After the electric field treatment, PtCu@BSA nanoparticles were degraded into Pt 2+ , Pt 4+ , Cu 2+ effect;

[0049] Figure 8 The effect of ROS production for Ctrl, E, PtCu@BSA, and PtCu@BSA+E groups;

[0050] Fig. 9 This is the degradation effect diagram of methylene blue under different dosage concentrations of PtCu@BSA;

[0051] Fig.10 The staining images of live and dead bacteria after treatment of different examples of Ctrl, E, PtCu, and PtCu+E groups;

[0052] Fig.11 Bacterial morphology of MRSA after treatment for different sample groups;

[0053] Fig.12 X-ray images of the tibia of rats in each experimental group;

[0054] Fig.13 These are thermal imaging images of inflammation in rats in each experimental group. DETAILED DESCRIPTION

[0055] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0056] The invention provides a PtCu@BSA nanoparticle, which comprises a porous PtCu-based nanoparticle and BSA, wherein the BSA is coated on the surface of the porous PtCu-based nanoparticle.

[0057] In the present invention, the porous PtCu-based nanoparticles are porous PtCu-based nanoparticles with mesopores. Mesopores refer to porous nanomaterials with a pore size of 10 to 50 nm. The pore size of the porous PtCu-based nanoparticles can be, for example, any one of 10, 15, 20, 30, 35, 40, 50 nm or a range value between any two of them. The porous PtCu-based nanoparticles in the present invention are made by a soft film method, and are porous PtCu-based nanoparticles with mesopores synthesized using Pluronic F-127 as a template.

[0058] When the pore size of the porous PtCu-based nanoparticles is less than 2nm, it is called small mesopores, and when the pore size is greater than 50nm, it is called large mesopores. In the present invention, by controlling the pore size of the porous PtCu-based nanoparticles to 10-50nm, better electrokinetic catalytic activity and antibacterial performance can be obtained. The porous PtCu-based nanoparticles can produce toxic hydroxyl radicals under electrokinetic catalysis, leading to bacterial death. At the same time, during the electrokinetic catalysis process, the porous PtCu-based nanoparticles will partially degrade into positively charged ions such as: Pt 2+ , Pt 4+ , Cu 2+ , has strong biofilm penetration ability and synergistically regulates the infection microenvironment to eliminate local inflammation.

[0059] The present invention uses BSA (bovine serum albumin) to coat porous PtCu-based nanoparticles. BSA is a common serum protein that has good biocompatibility in vivo and is not easy to cause immune response. The effects and advantages of modifying the surface of porous PtCu-based nanoparticles with BSA include: increasing biocompatibility and improving stability. Specifically, BSA is a natural protein, and its presence can improve the biocompatibility of porous PtCu nanoparticles, reduce their immunogenicity in vivo, and make the nanoparticles more easily accepted in vivo, thereby improving biocompatibility. BSA molecules are wrapped on the surface of porous PtCu-based nanoparticles, which is conducive to forming a stable protective layer to prevent the nanoparticles from agglomerating and precipitating in the solution, thereby improving stability.

[0060] In some embodiments of the present invention, the loading amount of BSA is 0.1-5 mg BSA per 1 mg of porous PtCu-based nanoparticles; for example, it can be but not limited to any one of 0.1, 0.5, 1, 2, 3, 4 or 5 mg or a range between any two of them, preferably 1 mg of porous PtCu-based nanoparticles is loaded with 2 mg BSA.

[0061] In some embodiments of the present invention, the particle size of the PtCu@BSA nanoparticles is 50 to 500 nm; the particle size may be, for example but not limited to, 50, 100, 150, 200, 250, 300, 350, 400, 450 or 500 nm, or a range between any two of the above points, preferably about 120 nm.

[0062] In some embodiments of the present invention, the potential of the PtCu@BSA nanoparticles is -20 to -10 mV.

[0063] The method for preparing the PtCu@BSA nanoparticles comprises wrapping BSA on the surface of porous PtCu-based nanoparticles.

[0064] Specifically, the steps include:

[0065] S1. Synthesis of porous PtCu-based nanoparticles.

[0066] In the present invention, Pluronic F-127 is used as a template to synthesize porous PtCu-based nanoparticles. The porous platinum-based nanoparticles synthesized by Pluronic F-127 do not use any toxic reagents and have high biocompatibility and nanoparticle yield.

[0067] Specifically, chloroplatinic acid, copper chloride, Pluronic F-127 and acid are mixed and dissolved, an α-ascorbic acid aqueous solution is added, and the mixed system is heated to react. The reaction temperature of the mixed system is 90-100°C, the reaction time is 3-5h, and the solution reacts until the solution turns black, and the porous PtCu-based nanoparticles are obtained by solid-liquid separation.

[0068] The concentration of chloroplatinic acid is 15-25 mM, for example, but not limited to 15, 18, 20, 22 or 25 mM, or a concentration range between any two of the above points, more preferably 20 mM.

[0069] The concentration of copper chloride is 15-25 mM, for example, but not limited to 15, 18, 20, 22 or 25 mM, or a concentration range between any two of the above points, more preferably 20 mM.

[0070] The concentration of Pluronic F-127 is 7.4-7.6 mg / mL, for example, but not limited to 7.2, 7.3, 7.4, 7.5, or 7.6 mg / mL, or a concentration range between any two of the above points. In an optional embodiment, the concentration of Pluronic F-127 is 7.4 mg / mL.

[0071] The acid includes but is not limited to at least one of hydrochloric acid, sulfuric acid, and nitric acid, preferably hydrochloric acid. The concentration of the hydrochloric acid is 4 to 8 M, for example, but not limited to 4, 5, 6, 7 or 8 M, or a concentration range between any two of the above points. In an optional embodiment, the concentration of the hydrochloric acid is 6 M.

[0072] The concentration of the α-ascorbic acid aqueous solution is 0.1-0.3 M; for example, it can be but not limited to 0.1, 0.2 or 0.3 M, or a concentration range between any two of the above points. In an optional embodiment, the concentration of hydrochloric acid is 0.1M.

[0073] S2. BSA is coated on the surface of porous PtCu-based nanoparticles.

[0074] (1) The porous PtCu-based nanoparticles are dissolved in an organic solvent, and lipoic acid is added to obtain PtCu-COOH nanoparticles.

[0075] The organic solvent includes C1-C4 low-carbon alcohols, and more preferably ethanol.

[0076] In the present invention, carboxyl groups can be grafted onto the porous PtCu-based nanoparticles by adding lipoic acid, so that the porous PtCu-based nanoparticles are carboxylated, thereby facilitating the subsequent compounding with BSA. The mass ratio of the porous PtCu-based nanoparticles to the lipoic acid is 1:8 to 12; the mass ratio can be, for example, any one of 1:8, 1:9, 1:10, 1:11, 1:12 or a range between any two of them, and more preferably 1:10.

[0077] The reaction time of the porous PtCu-based nanoparticles and lipoic acid is 10 to 15 hours; for example, it can be but not limited to 10, 11, 12, 13, 14 or 15 hours, or a time range between any two of the foregoing points, and more preferably 12 hours.

[0078] After obtaining the PtCu-COOH nanoparticles, they are washed and purified using an organic solvent to remove the porous PtCu-based nanoparticles and lipoic acid that have not been completely reacted on the surface.

[0079] (2) Dissolving PtCu-COOH nanoparticles in water, adding BSA and stirring to obtain PtCu@BSA nanoparticles, and washing and purifying the obtained PtCu@BSA nanoparticles with deionized water.

[0080] The mass ratio of porous PtCu-based nanoparticles to BSA is 1:8-12; for example, it can be 1:8, 1:9, 1:10, 1:11 or 1:12, or a time range between any two of the foregoing points, and more preferably 1:10. In the present invention, an excess of BSA is added during the preparation process to ensure that BSA can be fully loaded on the porous PtCu-based nanoparticles, and the loading amount is about 0.1-5 mg BSA per 1 mg of porous PtCu-based nanoparticles.

[0081] The reaction time of PtCu-COOH nanoparticles and BSA is 10 to 15 hours, for example, but not limited to, 10, 11, 12, 13, 14 or 15 hours, or a time range between any two of the foregoing points, more preferably 12 hours.

[0082] Before adding BSA, the method further includes adding EDC and NHS to the aqueous solution containing PtCu-COOH nanoparticles; wherein the total mass of EDC and NHS added is 5 to 15 times of the PtCu-COOH nanoparticles; for example, it can be but not limited to 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 times, or a mass range between any two of the foregoing points, and more preferably 10 times. The mass ratio of EDC to NHS is any mass ratio, including but not limited to 1:1, 1:4, 3:5, 5:1, etc.

[0083] The above-mentioned PtCu@BSA nanoparticles can be widely used in the preparation of drugs for treating osteomyelitis.

[0084] Correspondingly, the present invention provides a pharmaceutical composition for treating osteomyelitis, comprising the above-mentioned PtCu@BSA nanoparticles.

[0085] In an optional embodiment, the pharmaceutical composition further comprises an optional pharmaceutically acceptable adjuvant. In an optional embodiment, the pharmaceutically optionally acceptable adjuvant comprises one or more of a solvent, a solubilizer, a cosolvent, an emulsifier, a colorant, a disintegrant, a filler, an osmotic pressure regulator, a stabilizer, a glidant, a flavoring agent, an antibacterial agent, a suspending agent, a coating agent, an antioxidant, an antioxidant synergist, a chelating agent, a pH regulator, an adsorbent, a protective agent, a humectant, a softener, an absorbent, a diluent, a hollow capsule, a matrix and a carrier material.

[0086] In an optional embodiment, the pharmaceutical composition can be in any acceptable dosage form selected in the art, including but not limited to an injection dosage form or an oral dosage form.

[0087] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0088] The main reagents used in the following examples are as follows:

[0089] α-Ascorbic acid was purchased from Sigma-Aldrich (St. Louis, MO, USA).

[0090] N-(3-(Dimethylamino)-propyl)-3-ethylcarbodiamine hydrochloride (EDC) was purchased from Beijing Solai Biotechnology Co., Ltd. (Beijing, China).

[0091] N-Hydroxysuccinimide (NHS) was purchased from J&K Scientific Ltd. (Beijing, China).

[0092] Chloroplatinic acid (H 2 PtCl 6 ) and copper chloride (CuCl 2 ) was purchased from Chemical Technology Co., Ltd. (Tianjin, China).

[0093] BSA (fetal bovine serum albumin) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0094] All chemicals were used as received without further treatment.

[0095] Example 1

[0096] This embodiment provides a PtCu@BSA nanoparticle, and the preparation method thereof is as follows:

[0097] S1. Synthesis of porous PtCu-based nanoparticles.

[0098] 1.5 ml HO 2 PtCl 6 (20.0mM), 1.5ml CuCl 2 After mixing 0.2 ml of HCl (6.0 M) and 50.0 mg of Pluronic-F127, the mixture was dissolved under ultrasonic conditions, and 2.0 ml of ascorbic acid (0.1 M) aqueous solution was added to the above solution to obtain the final H 2 PtCI 6 、CuCl 2 The precursor amounts were 0.03 mmol and 0.03 mmol, respectively. Then, the mixed solution was kept in an oil bath at 95 °C for 4 hours. Finally, the sample was collected by centrifugation at 14000 rpm for 10 minutes, and the residual Pluronic-F127 was removed by continuous washing / centrifugation cycles with ethanol and water for multiple times to obtain porous PtCu-based nanoparticles. The prepared porous PtCu-based nanoparticles were stored in ethanol until dried at room temperature before use.

[0099] S2. BSA is coated on the surface of porous PtCu-based nanoparticles.

[0100] The porous PtCu-based nanoparticles were dissolved in ethanol, 10 times the mass of lipoic acid was added, and the reaction was carried out for 12 hours and then washed with ethanol for multiple times for purification. The obtained PtCu-COOH nanoparticles were then dissolved in water, and 10 times the mass of EDC and NHS of the nanoparticles were added to the prepared PtCu-COOH nanoparticle solution, followed by 10 times BSA, stirred for 12 hours, and finally, PtCu@BSA nanoparticles were obtained by centrifugation and washed with deionized water for multiple times for purification.

[0101] The transmission electron microscopy images and particle size distribution diagrams of the porous PtCu-based nanoparticles and PtCu@BSA nanoparticles prepared in this example are shown in FIG. Figure 1 As shown, the XRD pattern is Figure 2 As shown, the infrared absorption peak diagram is as follows Figure 3 shown.

[0102] In this embodiment, the particle size of the PtCu@BSA nanoparticles is about 115 nm, the potential of the porous PtCu-based nanoparticles is about -11.2 mV, the potential of BSA is -12.6 mV, and the potential of PtCu@BSA is -16.4 mV. The loading amount of BSA is 2 mg of BSA per 1 mg of porous PtCu-based nanoparticles.

[0103] Example 2

[0104] This embodiment provides a PtCu@BSA nanoparticle, and the preparation method thereof is as follows:

[0105] S1. Synthesis of porous PtCu-based nanoparticles.

[0106] 1 ml HO 2 PtCl 6 (25.0mM), 1ml CuCl 2 (25mM), 0.1ml HCl (8.0M) and 60.0mg Pluronic-F127 were mixed and dissolved under ultrasonic conditions, and 1.0ml ascorbic acid (0.3M) aqueous solution was added to the above solution. Then, the mixed solution was kept in an oil bath at 100°C for 3 hours. Finally, the sample was collected by centrifugation at 14000rpm for 10 minutes, and the residual Pluronic-F127 was removed by continuous washing / centrifugation cycles with ethanol and water for multiple times to obtain porous PtCu-based nanoparticles. The prepared porous PtCu-based nanoparticles were stored in ethanol until dried at room temperature when used.

[0107] S2. BSA is coated on the surface of porous PtCu-based nanoparticles.

[0108] The porous PtCu-based nanoparticles were dissolved in ethanol, 12 times the mass of lipoic acid was added, and the reaction was carried out for 15 hours and then washed with ethanol for multiple purification. The obtained PtCu-COOH nanoparticles were then dissolved in water, and 15 times the mass of the nanoparticles of EDC and NHS were added to the prepared PtCu-COOH nanoparticle solution, followed by 8 times of BSA, stirred for 15 hours, and finally, PtCu@BSA nanoparticles were obtained by centrifugation and washed with deionized water for multiple purification.

[0109] Example 3

[0110] This embodiment provides a PtCu@BSA nanoparticle, and the preparation method thereof is as follows:

[0111] S1. Synthesis of porous PtCu-based nanoparticles.

[0112] Add 2 ml HO 2 PtCl 6 (15.0mM), 2ml CuCl 2 (15mM), 0.3ml HCl (4.0M) and 40.0mg Pluronic-F127 were mixed and dissolved under ultrasonic conditions, and 3.0ml ascorbic acid (0.2M) aqueous solution was added to the above solution. Then, the mixed solution was kept in an oil bath at 90°C for 5 hours. Finally, the sample was collected by centrifugation at 14000rpm for 10 minutes, and the residual Pluronic-F127 was removed by continuous washing / centrifugation cycles with ethanol and water for multiple times to obtain porous PtCu-based nanoparticles. The prepared porous PtCu-based nanoparticles were stored in ethanol until dried at room temperature when used.

[0113] S2. BSA is coated on the surface of porous PtCu-based nanoparticles.

[0114] The porous PtCu-based nanoparticles were dissolved in ethanol, 8 times the mass of lipoic acid was added, and the reaction was carried out for 10 hours and then washed with ethanol for multiple purification. The obtained PtCu-COOH nanoparticles were then dissolved in water, and 5 times the mass of the nanoparticles of EDC and NHS were added to the prepared PtCu-COOH nanoparticle solution, followed by 12 times of BSA, stirred for 10 hours, and finally, PtCu@BSA nanoparticles were obtained by centrifugation and washed with deionized water for multiple purification.

[0115] Comparative Example 1

[0116] This comparative example provides a porous PdCu-based nanoparticle, and its preparation method is different from step S1 of Example 1 in that H is added to the precursor. 2 PtCl 6 (20.0mM) replaced with Na2 PdCl 4 (20.0mM). Data as Figure 4 .

[0117] from Figure 4 It can be seen that the particle size of the nanoparticles is about 110nm. Figure 6 It can be seen that the nanoparticles are platinum, copper, and palladium trimetallic nanoparticles. Experiments on the degradation of methylene blue show that the degradation effect of the nanoparticles on methylene blue under the action of an alternating electric field is lower than that of PtCu@BSA prepared in Example 1.

[0118] Comparative Example 2

[0119] This comparative example provides a large mesoporous PtNPs nanoparticle, and the preparation method thereof is as follows:

[0120] DPPC and cholesterol were dissolved in chloroform and subjected to rotary evaporation. When the solution was evaporated to a white film, an α-ascorbic acid aqueous solution was added to fully dissolve the white solid. After the dissolution was complete, the solution was ultrasonicated to a clear liquid. Subsequently, chloroplatinic acid solution was added to the solution and reacted for 6 hours. The solution eventually turned black. The nanoparticles were washed three times by centrifuge at 10000RPM for 10 minutes to prepare PtNPs nanoparticles. Data as shown in Figure 6 .

[0121] from Figure 5 It can be seen that the particle size of the nanoparticles is about 100 nm. Figure 6 It can be seen that the nanoparticles are pure platinum metal nanoparticles. The experiment on the degradation of methylene blue shows that the degradation effect of the nanoparticles on methylene blue under the action of the alternating electric field is lower than that of the PtCu@BSA prepared in Example 1.

[0122] Experimental Example 1: Verification of the ability of PtCu@BSA nanoparticles to generate ROS

[0123] The electrocatalytic activity of the nanoparticles was evaluated by measuring the absorption change of the methylene blue solution at 664 nm during the catalytic decomposition of the dye. In a typical process such as photocatalysis, 2 ml of MB dye (3 × 10 -5 MB) and PtCu@BSA (100 μg / ml) in PBS were placed in cells in a 24-well plate. The cell was equipped with symmetrically arranged platinum electrodes connected to the wells via a salt bridge (f = 3 mm, saturated KCI). The two electrodes were connected to a DC power supply and its intensity was monitored by a multimeter. The square wave AC output was achieved by the forward and reverse components of a DC motor. The current duration was controlled to be 1 second, 10 seconds, 30 seconds or 60 seconds. After the power was turned on, 50 μl of the mixture was extracted, diluted 4 times, and the absorption spectrum of MB was measured.

[0124] from Figure 7 It can be seen that after applying the electric field, part of the PtCu@BSA nanoparticles degraded into Pt 2+ , Pt 4+ , Cu 2+ .

[0125] from Figure 8 It can be seen that PtCu@BSA nanoparticles have a strong ability to generate ROS under the action of electric field.

[0126] from Fig. 9 It can be seen that PtCu@BSA has a degradation effect on methylene blue at different dosage concentrations (the effect of methylene blue degradation is used to evaluate the ROS generation effect).

[0127] Experimental Example 2: Verification of the antibacterial properties of PtCu@BSA nanoparticles

[0128] Based on the excellent electrokinetic catalytic activity of PtCu@BSA nanoparticles, the present invention studied the antibacterial properties of PtCu@BSA nanoparticles against MRSA, which is the main cause of osteomyelitis. Live / dead staining assay was performed using CLSM to study the effective antibacterial activity of PtCu@BSA nanoparticles. Live and dead bacteria were stained with syringin orange (SYTO, green fluorescence) and propidium iodide (PI, red fluorescence), respectively, and then observed by CLSM. Fig.10 As shown, the bacteria in the control group (Ctrl) emit green fluorescence, indicating that all bacteria are alive. The bacteria in the EDT electric field group (E) and the PtCu@BSA nanoparticle group (PtCu@BSA) emit green fluorescence, indicating that all bacteria are alive. When the EDT electric field is activated, almost all bacteria in the PtCu@BSA group (PtCu@BSA+E) show red fluorescence, indicating that the electrodynamic effect mediated by PtCu@BSA effectively damages MRSA. The bacterial morphology of MRSA after these treatments was observed under a scanning electron microscope, as shown in Fig.11 As shown in Figure 2, the bacterial surface of the control group has a complete and smooth membrane structure, while the cell wall of the bacteria in the PtCu@BSA+E group appears wrinkled and broken and due to the positively charged ions (Pt 2+ , Pt 4+ , Cu 2+ ) release leads to the death of a large number of bacteria.

[0129] Experimental Example 3: Animal Experiment

[0130] Animal experimental procedures: We locally injected PtCu@BSA nanoparticles into rats with osteomyelitis model and applied (10mHZ / 5mA) alternating electric field treatment to the infected area of ​​osteomyelitis in rats through an electric field generator for 10 minutes each time.

[0131] After twice weekly treatment, X-rays of the tibiae of rats with osteomyelitis were taken on days 0 and 21 of treatment to evaluate the relief of the infection site. Fig.12 It can be clearly seen that the PtCu@BSA+E group had the best effect, with better bone density and bone morphology than other groups, which also proves that the symptoms have been significantly improved.

[0132] After the treatment cycle, the rats in different groups were subjected to thermal imaging using the animal thermal imaging verification method. Fig.13 It can be seen that the temperature of PtCu@BSA+E in the rat tibia is lower than that in other groups, which also proves that PtCu@BSA+E has a certain degree of relief on inflammation.

[0133] In summary, the PtCu@BSA nanoparticles provided by the present invention use porous PtCu-based nanoparticles as the skeleton, and the surface of the nanoparticles is coated with BSA. Modifying the surface of the porous PtCu-based nanoparticles with BSA is beneficial to enhancing the biocompatibility and stability of the PtCu@BSA nanoparticles. At the same time, the porous PtCu-based nanoparticles have high targeting ability and electrokinetic catalytic effect. Under the action of the alternating current electric field, they can well catalyze the decomposition of water into hydroxyl radicals, thereby effectively killing bacteria and improving the limitations of the existing osteomyelitis treatment drugs that frequently use antibiotics. At the same time, during the electrokinetic catalysis process, the porous PtCu-based nanoparticles will partially degrade into positively charged ions such as: Pt 2+ , Pt 4+ , Cu 2+ , these ions have strong biomembrane penetration, these ions can synergistically regulate the infection microenvironment to reduce local inflammation. Compared with small molecule drugs, PtCu@BSA nanoparticles have better stability in the body, so they can increase drug circulation time and reduce the frequency of administration.

[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A PtCu@BSA nanoparticle, characterized in that: The invention comprises porous PtCu-based nanoparticles and BSA, wherein the BSA is coated on the surface of the porous PtCu-based nanoparticles.

2. The PtCu@BSA nanoparticles according to claim 1, characterized in that The pore size of the porous PtCu-based nanoparticles is 10 to 50 nm; Preferably, the porous PtCu-based nanoparticles are synthesized using Pluronic F-127 as a template.

3. The PtCu@BSA nanoparticles according to claim 1, characterized in that The loading amount of the BSA is 0.1 to 5 mg of the BSA per 1 mg of the porous PtCu-based nanoparticles; Preferably, the encapsulation efficiency of BSA is 130-150%; Preferably, the particle size of the PtCu@BSA nanoparticles is 110-120 nm; Preferably, the potential of the PtCu@BSA nanoparticles is -20 to -10 mV.

4. A method for preparing PtCu@BSA nanoparticles according to any one of claims 1 to 3, characterized in that: The BSA is coated on the surface of the porous PtCu-based nanoparticles.

5. The method for preparing PtCu@BSA nanoparticles according to claim 4, characterized in that: The method for preparing the porous PtCu-based nanoparticles comprises: synthesizing using Pluronic F-127 as a template; Preferably, the method for preparing the porous PtCu-based nanoparticles comprises dissolving chloroplatinic acid, cupric chloride, Pluronic F-127 and acid in a mixed solution, adding an α-ascorbic acid aqueous solution, heating the mixed system to react, reacting the solution until the solution turns black, and separating the solid from the liquid to obtain the porous PtCu-based nanoparticles; Preferably, the amount ratio of the chloroplatinic acid, the cupric chloride, the Pluronic F-127, the acid and the α-ascorbic acid aqueous solution is 1-2 ml: 1-2 ml: 40-60 mg: 0.1-0.3 ml: 1-3 ml; Preferably, the reaction temperature of the mixed system is 90-100°C and the reaction time is 3-5h; Preferably, the concentration of the α-ascorbic acid aqueous solution is 0.1-0.3M; Preferably, the concentration of chloroplatinic acid is 15-25 mM, more preferably 20 mM; Preferably, the concentration of copper chloride is 15-25 mM, more preferably 20 mM; Preferably, the concentration of Pluronic F-127 is 7.4-7.6 mg / mL, more preferably 7.4 mg / mL; Preferably, the concentration of the acid is 4-8M.

6. The method for preparing PtCu@BSA nanoparticles according to claim 4, characterized in that: The BSA is coated on the surface of the porous PtCu-based nanoparticles comprising: dissolving the porous PtCu-based nanoparticles in an organic solvent, adding lipoic acid, and obtaining PtCu-COOH nanoparticles; The PtCu-COOH nanoparticles are dissolved in water, and the BSA is added and stirred to obtain PtCu@BSA nanoparticles.

7. The method for preparing PtCu@BSA nanoparticles according to claim 6, characterized in that: The organic solvent includes C1-C4 low-carbon alcohol; Preferably, the mass ratio of the porous PtCu-based nanoparticles to the lipoic acid is 1:8-12; the mass ratio of the porous PtCu-based nanoparticles to the BSA is 1:8-12; Preferably, the reaction time of the porous PtCu-based nanoparticles and the lipoic acid is 10 to 15 hours; the reaction time of the PtCu-COOH nanoparticles and the BSA is 10 to 15 hours.

8. The method for preparing PtCu@BSA nanoparticles according to claim 6, characterized in that: Before adding the BSA, the method further includes adding EDC and NHS to the aqueous solution containing the PtCu-COOH nanoparticles; Preferably, the total added mass of the EDC and the NHS is 5 to 15 times that of the PtCu-COOH nanoparticles; Preferably, after obtaining the PtCu-COOH nanoparticles, they are washed and purified using an organic solvent; Preferably, after obtaining the PtCu@BSA nanoparticles, they are washed and purified with deionized water.

9. Use of the PtCu@BSA nanoparticles according to any one of claims 1 to 3 or the method for preparing the PtCu@BSA nanoparticles according to any one of claims 4 to 8 in preparing a drug for treating osteomyelitis.

10. A pharmaceutical composition for treating osteomyelitis, characterized in that: It comprises the PtCu@BSA nanoparticles as described in any one of claims 1 to 3; Preferably, the pharmaceutical composition for treating osteomyelitis further comprises a pharmaceutically acceptable excipient; Preferably, the pharmaceutically acceptable excipients include one or more of solvents, solubilizers, cosolvents, emulsifiers, colorants, disintegrants, fillers, osmotic pressure regulators, stabilizers, glidants, flavoring agents, antibacterial agents, suspending agents, coating agents, antioxidants, antioxidant synergists, chelating agents, pH regulators, adsorbents, protective agents, humectants, softeners, absorbents, diluents, empty capsules, matrix and carrier materials; Preferably, the dosage form of the pharmaceutical composition for treating osteomyelitis includes an injection form or an oral dosage form.

Citation Information

Patent Citations

  • TF (at) Pt-Aln nanoparticles as well as preparation method and application thereof

    CN117281921A

Cited By

  • Bionic scaffold based on PtCu nanowire-nSi-mineralized collagen fiber and preparation method thereof

    CN120346372A